2000
DOI: 10.1046/j.1464-410x.2000.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

A new staging criterion for bladder carcinoma using gadolinium‐enhanced magnetic resonance imaging with an endorectal surface coil: a comparison with ultrasonography

Abstract: Objective To evaluate the accuracy of a new staging criterion, submucosal linear enhancement (SLE) on gadolinium-diethylenetriamine-pentaacetic acidenhanced T1-weighted magnetic resonance imaging (MRI) using an endorectal surface coil (endorectal enhanced MRI), and to compare the accuracy of this method with that of transurethral ultrasonography (TUUS). Patients and methods The study included 71 patients with bladder tumours (63 men and eight women, mean age 65.5 years, range 31±85). The SLE coincided with abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 17 publications
0
39
1
Order By: Relevance
“…It has been reported in numerous publications that Gd chelates improve sensitivity, specificity and diagnostic accuracy of MR procedures [5,21,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60]. Indications for their use include the evaluation of tumoral, traumatic and infectious disease processes.…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported in numerous publications that Gd chelates improve sensitivity, specificity and diagnostic accuracy of MR procedures [5,21,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60]. Indications for their use include the evaluation of tumoral, traumatic and infectious disease processes.…”
Section: Indicationsmentioning
confidence: 99%
“…The combined use of Gd chelates and breathhold imaging (increased tumour-to-parenchyma contrast ratio) results in better tumour detection in most organs, as compared with unenhanced MR imaging. Most MR information for characterizing liver [44,45] and renal [53,54] tumours, and in the pretherapeutic assessment of uterine [55], ovarian [56], bladder and prostate tumours [57,58]. Controversies remain concerning the best contrast agent for MR imaging of the liver, either for detection or characterization: extracellular compounds; superparamagnetic particles; manganese or gadobenate dimeglumine which has a nonspecific extracellular phase followed by specific uptake by functioning hepatocytes prior to its excretion into the bile.…”
Section: Abdomen and Pelvismentioning
confidence: 99%
“…19 Recently, it has been reported that cross-sectional imaging is only useful after the tumor escapes beyond the bladder wall. 20 Thereby, it was reported in a recent study by Hayashi et al 14 that CT cannot distinguish between tumors with stages lower than T2b.…”
Section: Discussionmentioning
confidence: 98%
“…20 Furthermore, conventional MRI was reported in the aforementioned study by Hayashi et al 14 to be ineffective for differentiation of both stage Ta from stage T1 and stage T2a from stage T2b. In the same study, the authors reported accuracy of 66% and sensitivity of 78% for muscle invasion using TUUS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation